Prognostic Impact of Tumor Solid Components in Stereotactic Body Radiotherapy for Clinical Stage Tis–1N0M0 Lung Cancer - Junki Fukuda; Hiroshi Doi; Atsushi Kono; Takaya Inagaki; Naoko Ishida Hamazawa; Saori Tatsuno Imamura; Takuya Uehara; Masahiro Inada; Kiyoshi Nakamatsu; Makoto Hosono; Kazunari Ishii; Yukinori Matsuo (Thoracic Cancer)
ABSTRACT Purpose This study aimed to assess the potential of prognostic factors including consolidation tumor ratio (CTR) on treatment outcomes in patients with clinical stage 0–IA non‐small cell lung cancer (NSCLC) undergoing stereotactic body radiotherapy (SBRT). Methods The analysis included data of 63 patients with 67 lesions of clinical stage 0–IA NSCLC treated with SBRT. According to the Union for International Cancer Control 8th edition, the following tumor stages were observed: Tis, 3; T1mi, 2; T1a, 11; T1b, 29; and T1c, 22. The prescribed dose was 48 (range, 42–52) Gy in four fractions. Results The median follow‐up was 29.3 (range: 2.4–120.5) months. The five‐year local control (LC), overall survival, and progression‐free survival (PFS) rates were 89.4%, 60.3%, and 40.5%, respectively. Squamous cell carcinoma (Sq) and Dmax < 125 GyBED10 for planning target volume (PTV) were associated with a worse LC (p = 0.001 and 0.017, respectively). Patients with Sq, T1b–c, CTR > 0.25, PTV ≥ 30 cm3 tumors were associated with worse PFS than those with non‐Sq, ≤ cT1a, CTR ≤ 0.25, PTV < 30 cm3 tumors (p = 0.049, 0.004, 0.038, and 0.004, respectively). No recurrences, metastases, or deaths were found in patients with CTR ≤ 0.25 (n = 5). Conclusion In patients with stage 0–IA lung cancer treated with SBRT, tumors classified as ≤ T1a showed a better PFS than T1b–c. NSCLC with a low CTR of ≤ 0.25 seemed to have a low risk of recurrence after SBRT.